Chemical attributes of percolate from degraded sand soil irrigated with treated industrial wastewater. Issue 3 (7th May 2021) - Carlos, Filipe Selau; Schaffer, Naihana; Tedesco, Marino José; Weinert, Cristiano; Reginato, Julia Lima; de Sousa, Rogério Oliveira; Boechat, Cacio Luiz; Andreazza, Robson; de Oliveira Camargo, Flávio Anastácio
Abstract: Applying treated industrial tannery wastewater to soil can be an important practice for its disposal and aid in the recovery of degraded soils. This study aimed to evaluate the chemical attributes of the percolate of degraded soil irrigated with treated industrial wastewater (TIW). The experiment was carried out in a greenhouse, using soil‐filled polyvinyl chloride columns. The treatments consisted of TIW at increasing rates (0%, 25%, 50%, 75%, and 100%) and organomineral and organic fertilization. Irrigation with treated wastewater on soil degraded by clay extraction increased mineral nitrogen, biochemical oxygen demand (BOD), electrical conductivity, sodium, and sodium adsorption ratio in percolate under maize cultivation. Irrigation with TIW increased mineral nitrogen and BOD in the percolate by 34% and 25%, respectively, relative to the control treatment (plain water). Concentrations of total nitrogen and BOD must be less than 100 and 65 mg L –1, respectively, to minimize the potential contamination of water bodies. The degraded soil and maize ( Zea mays L.) cultivation reduced the total mineral nitrogen and BOD in the percolate by 96% and 84%, respectively. The sodium adsorption ratio had a high removal efficiency of 79% of the percolate when compared to TIW.